Association between osteoarthritis with Parkinson’s disease in the US (NHANES 2011–2020) - Liu, Yang; Zhou, Xue; Chen, Chunhai; Li, Xuefeng; Pan, Ting; Liu, Ziqi; Wu, Dalong; Chen, Xinhua (Frontiers in Neuroscience, 2024)
Objected To evaluate the association between osteoarthritis (OA) and Parkinson’s disease (PD) in adults in the United States. Methods Using 2011–2020 NHANES data, a cross-sectional study of 11,117 adults over the age of 40 was conducted. Univariate logistic regression and multivariate logistic regression were used to analyze the relationship between arthritis and PD. In addition, stratified analysis was used to examine whether the relationship between arthritis and PD was interactive with age, gender, race, education, BMI. Results In this study, a total of 11,117 participants were included, and we found that osteoarthritis was positively correlated with the development of PD compared with non-arthritis patients [1.95 (1.44 ~ 2.62)] (p < 0.001). After adjusting the covariates, the results are still stable. Conclusion PD patients were positively correlated with OA. Among people with OA, there was a 95% increased risk of PD compared to people without arthritis. Therefore, when treating OA, attention should be paid to the increased risk of PD. In the meantime, further studies are needed to explore the link between OA and PD patients.